Meeting standards through integrated curriculum - Drake, Susan M., 1944- (Association for Supervision and Curriculum Development, 2004)
Many schools under pressure to meet new standards of learning mistakenly believe that they must adopt a narrow curriculum that imposes strict boundaries on what students are taught. In this book, Susan M. Drake and Rebecca C. Burns address this issue by offering strategies for synchronizing standards across the disciplines. At the heart of the book is the KNOW/DO/BE framework, which teachers can use to ensure a curriculum that is both rigorous and relevant to K-12 students at all stages of proficiency. Among other things, this comprehensive framework allows teachers to: . Map curriculum . Scan and cluster standards . Develop assessments and guiding questions . Align integrated instructional strategies and assessments Though the authors draw much of their data from research on integration, their focus is on analyzing the real-life experiences of teachers who have successfully integrated their curricula in the service of accountability. The many benefits of this approach that the authors explore include lower absenteeism, fewer behavioral problems, and higher rates of homework completion among students. By combining case studies with a wealth of supporting research, Meeting Standards Through Integrated Curriculum offers teachers a user-friendly system for meeting standards while advancing broad-based learning.